Multiwavelength generation using an add-drop microring resonator integrated with an InGaAsP/InP sampled grating distributed feedback - Alavi, S.E.; Amiri, I.S.; Soltanian, M.R.K.; Penny, R.; Supa'at, A.S.M.; Ahmad, Harith (Optical Society of America, 2016)
A system of an add-drop microring resonator integrated with a sampled grating distributed feedback (SG-DFB) is investigated via modeling and simulation with the time-domain traveling wave (TDTW) method. The proposed microring resonator comprises a SiO2 waveguide integrated with an InGaAsP/InP SG-DFB, and the SiO2 waveguide consists of a silicon core having a refractive index of 3.48 and Kerr coefficient of 4.5 × 10-18 m2/W. The SG-DFB consists of a series of grating bursts that are constructed using a periodic apodization function with a burst spacing in the grating of 45 μm, a burst length of 5 μm, and 10 bursts across the total length of the SG-DBR. Transmission results of the through and drop port of the microring resonator show the significant capacity enhancement of the generated center wavelengths. The Q-factor of the microring resonator system, defined as the center wavelength (λ0) divided by 3 dB FWHM, without and with integration with the SG-DFB is calculated as 1.93 × 105 and 2.87 × 105, respectively. Analysis of the dispersion of the system reveals that increasing the wavelength results in a decrease of the dispersion. The higher capacity and efficiency are the advantages of integrating the microring resonator and the InGaAsP/InP SG-DFB.